1999
DOI: 10.1021/jf980715+
|View full text |Cite
|
Sign up to set email alerts
|

Free and Conjugated Polyamines and Phenols in Raw and Alkaline-Clarified Sugarcane Juices

Abstract: Sugarcane juice contains a lot of sucrose associated with several monosaccharides, defined as low molecular mass carbohydrates (LMMC), as well as some polysaccharides and glycoproteins, which are defined as mid and high molecular mass carbohydrates (MMMC and HMMC, respectively). These three categories of carbohydrates can be separated by size-exclusion chromatography through Sephadex G-10 and Sephadex G-50 columns, but elution profiles change drastically after juice clarification performed by adjusting the pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 31 publications
3
21
0
Order By: Relevance
“…This could also be seen in the initial settling rates where higher ISRs were observed in the WPT than in the NPT cane juices (Table 6). This was in agreement with studies by Eggleston, Monge, and Pepperman (2002) and de Armas et al (1999) who reported formation of larger flocs and faster settling rates leading to higher turbidity removal upon preheating of the mixed cane juice before liming. These results therefore suggest that incorporating alum in WPT intermediate liming has a great potential for turbidity removal in cane juice clarification.…”
Section: Turbidity Measurementsupporting
confidence: 93%
See 2 more Smart Citations
“…This could also be seen in the initial settling rates where higher ISRs were observed in the WPT than in the NPT cane juices (Table 6). This was in agreement with studies by Eggleston, Monge, and Pepperman (2002) and de Armas et al (1999) who reported formation of larger flocs and faster settling rates leading to higher turbidity removal upon preheating of the mixed cane juice before liming. These results therefore suggest that incorporating alum in WPT intermediate liming has a great potential for turbidity removal in cane juice clarification.…”
Section: Turbidity Measurementsupporting
confidence: 93%
“…However, as observed in Table 2 there was a mean decrease in invert sugar concentrations from the MJ to the AFTINCB samples. The one and a half minute heating time probably minimised inversion and could be that some invert sugars may have been removed with heatinduced precipitation of colloids, macromolecules (starch, dextran polysaccharides and proteins) and colour (de Armas, Martinez, Vicente, & Legaz, 1999;Saska, Zossi, & Liu, 2010a). The decrease in • Brix from the MJ to the AFTINCB could be further evidence of this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elution was carried out also with MilliQ-grade water. The void volume (22 mL) was discarded whereas the following 14 mL contained both HMMG and MMMG (de Armas et al, 1999), defined as glycoproteins after separation by HPLC and carbohydrate and fluorescence emission analyses. Two filtration processes were required to obtain 28 mL of these glycoproteins.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to presence of Cad in various plants, it is reported in table olive, 34 sugarcane juice. 11,35 It is challenging to define the relevance of Cad in these products. The variability in content is a less understood and remain unelucidated in terms of physiochemical significance.…”
Section: Introductionmentioning
confidence: 99%